7(n-2)-(3-4n)=10n

Simple and best practice solution for 7(n-2)-(3-4n)=10n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(n-2)-(3-4n)=10n equation:


Simplifying
7(n + -2) + -1(3 + -4n) = 10n

Reorder the terms:
7(-2 + n) + -1(3 + -4n) = 10n
(-2 * 7 + n * 7) + -1(3 + -4n) = 10n
(-14 + 7n) + -1(3 + -4n) = 10n
-14 + 7n + (3 * -1 + -4n * -1) = 10n
-14 + 7n + (-3 + 4n) = 10n

Reorder the terms:
-14 + -3 + 7n + 4n = 10n

Combine like terms: -14 + -3 = -17
-17 + 7n + 4n = 10n

Combine like terms: 7n + 4n = 11n
-17 + 11n = 10n

Solving
-17 + 11n = 10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-10n' to each side of the equation.
-17 + 11n + -10n = 10n + -10n

Combine like terms: 11n + -10n = 1n
-17 + 1n = 10n + -10n

Combine like terms: 10n + -10n = 0
-17 + 1n = 0

Add '17' to each side of the equation.
-17 + 17 + 1n = 0 + 17

Combine like terms: -17 + 17 = 0
0 + 1n = 0 + 17
1n = 0 + 17

Combine like terms: 0 + 17 = 17
1n = 17

Divide each side by '1'.
n = 17

Simplifying
n = 17

See similar equations:

| 3(31x-42)=62+31 | | 1/3(15a-3)=5A-1 | | 5=3v | | 5m=115 | | 65433333333343252+3x*x*x=x-72376237-x | | -4j+3=15 | | -185+35t=0 | | ln(2x+4)=3.6 | | 12=0.76x | | 3x^2+8x-33=0 | | -2a+12=-2 | | 3(x+6)=4x-x+2 | | 3.1m=-12.4 | | 216=w^3 | | 9d-18=58 | | 3.1m=-12.5 | | 60+5n=2n | | 5x-10=5(x+4) | | 5w-27=28 | | 4=-2g | | .4n=12 | | -x/24=4 | | 2c+(3c+-4)=5c+-4 | | 6=r-7 | | y=9x+3x | | Z-5-13= | | X+(-8)=-16 | | 3y+15=36 | | 2c+(3c+-4)=4c+-4 | | -4(n+2)=-5n | | (8x^4y^2/3z^3)*(9xy^2z^6/4y^4) | | 1.21=11(0.5+0.4x)whatisx |

Equations solver categories